2004
DOI: 10.1023/b:inte.0000018545.62455.ff
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Complex Retinal Detachment Surgery after Silicone Oil Removal

Abstract: The residual vitreoretinal traction especially at the vitreous base is the most likely reason for retinal redetachment after silicone oil removal, which is most commonly seen during the first 10 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…The incidence is widely variable: most studies have reported an incidence of 20–25%,1 6 8 9 11 some 15–20%,4 10 and a few below 10% 2 5 13. Several mechanisms have been advocated for redetachment: reopening of pre-existing breaks, posterior migration of an occult RD or new retinal break formation,6 and residual vitreoretinal traction at the vitreous base 13. To reduce the incidence of RD, application of an encircling band or laser treatment of different extent (ranging from panphotocoagulation to treatment from the equator to the ora serrata, to 360° laser in three or four rows) has been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence is widely variable: most studies have reported an incidence of 20–25%,1 6 8 9 11 some 15–20%,4 10 and a few below 10% 2 5 13. Several mechanisms have been advocated for redetachment: reopening of pre-existing breaks, posterior migration of an occult RD or new retinal break formation,6 and residual vitreoretinal traction at the vitreous base 13. To reduce the incidence of RD, application of an encircling band or laser treatment of different extent (ranging from panphotocoagulation to treatment from the equator to the ora serrata, to 360° laser in three or four rows) has been used.…”
Section: Discussionmentioning
confidence: 99%
“…SO removal is followed by a redetachment in up to 30% of eyes,1 – 14 with the incidence being influenced by many factors, including the type of RD, the number of previous retinal surgeries and also the surgeon 9. RD occurs usually in the first 3 months:15 16 the proposed mechanisms include reopening of pre-existing breaks, posterior migration of an occult RD, formation of new retinal breaks6 and vitreoretinal traction at the vitreous base 13…”
mentioning
confidence: 99%
“…Others have found that 20% of these will have a recurrence of retinal detachment. [7][8][9] Other relevant studies with the exception of that of Sullivan et al 1 relate to buckling surgery from the early 1980s and conventional surgery was used in 101 of 153 (66%) of Sullivan's patients. In our study conventional surgery was used in only 30%.…”
Section: Statistically Significant Factors Predicting Visual Outcomementioning
confidence: 99%
“…The mechanisms of pars plana sclerotomy-related RD involve the intraoperative formation of new retinal breaks 3 and vitreoretinal traction of the vitreous base. 4 Prevalence rates of postvitrectomy RD have been reported from 1.7% to 11%, 5-10 and scleral buckling, 11 panretinal photocoagulation, 12,13 and 360°laser retinopexy [14][15][16] are procedures to prevent it. However, scleral buckling can induce complications, such as eyeball perforation, eyeball disfigurement, myopia, and intraocular pressure elevation, and panretinal photocoagulation can induce complications, such as macular edema, visual acuity decrease, visual field constriction, and choroidal hemorrhage.…”
mentioning
confidence: 99%